Effect of traffic knowledge on the efficiency of admission-control policies. - Trajković, Ljiljana (Computer communication review.)
We investigate the importance of understanding traffic characteristics for admission-control policies in packet networks. We compare the network utilization achieved with admission policies based on a partial knowledge of admitted traffic against the utilization that could be achieved with complete knowledge of traffic characteristics. Our quantitative study demonstrates that for realistic traffic traces the level of traffic knowledge dramatically affects admission control and improves network utilization. Indeed, the knowledge of only a few elementary traffic characteristics can produce substantial improvement. Yet, at least for one trace, this improvement based on elementary traffic knowledge is modest in comparison with the improvement that could be produced with additional traffic knowledge and if traffic characterization on more than one time scale were available.